The relationship of stress coping styles on substance use, depressive symptoms, and personality traits of nurses in higher education institution - Keita Tokumitsu; Norio Sugawara; Hiroaki Okayasu; Yasushi Kawamata; Masataka Shinozaki; Yoshiteru Sato; Aoi Sato; Yumiko Uchibori; Tomie Komatsu; Norio Yasui‐Furukori; Kazutaka Shimoda (Wiley, 2023)
Abstract Aim This study examined the collective characteristics of nurses and their stress coping style. Methods We conducted a cluster analysis of the stress coping strategies of 841 nurses belonging to Dokkyo Medical University Hospital, as measured by the Brief COPE (Coping Orientation to Problems Experienced). We also conducted multivariate analyses of each cluster's sociodemographic characteristics, personality traits, depressive symptoms, work attitudes, sense of fairness, and turnover intention. Results The results of cluster analysis using the standardized z scores of the Brief COPE demonstrated that the study participants were classified into three clusters. The "emotional‐response type" tended to favor the use of emotional support, venting, and self‐blame. The "reality‐escape type" tended to prefer alcohol and substance use, behavioral resignation, use of instrumental support, and lack of acceptance. The "problem‐solving type" tended to prefer planning, positive reframing, and acceptance and to dislike "alcohol and substance use" and behavioral disengagement. A multinomial logistic regression analysis revealed that compared to the problem‐solving type, the emotional‐response type had a lower job title, a higher "neuroticism" score on the TIPI‐J, and a higher K6 score. However, compared to the problem‐solving type, the reality‐escape type was younger, consumed more alcohol and substances, and had a higher K6 score. Conclusions Stress coping styles were found to be associated with substance use, depressive symptoms, and personality traits among nurses in higher education institutions. Thus, the results suggest that nurses who choose maladaptive stress coping styles require mental support and early identification of depressive symptoms and alcohol problems.